Effectiveness of a blended learning intervention in cardiac physiotherapy. A randomized controlled trial - Marques-Sule, Elena; Sánchez-González, Juan Luis; Carrasco, Juan J.; Pérez-Alenda, Sofía; Sentandreu-Mañó, Trinidad; Moreno-Segura, Noemí; Cezón-Serrano, Natalia; Ruiz de Viñaspre-Hernández, Regina; Juárez-Vela, Raúl; Muñoz-Gómez, Elena (Frontiers in Public Health, 2023)
Blended learning (BL) combines both face-to-face learning (FL) and online learning. This study aimed at comparing the effectiveness of a BL intervention versus a FL intervention in physiotherapy students on knowledge, competencies, satisfaction, perceptions, usability and BL acceptance. An assessor-blinded randomized trial was performed. A total of 100 students were randomly allocated to a BL group (BLG, n=48), or a FL group (FLG, n=52). The BLG received face-to-face classes plus online resources (online syllabus, Moodle, scientific-based videos and websites, activities, glossary, and apps). The FLG received face-to-face classes and hardcopy re-sources (hardcopy syllabus, scientific-based information, activities, and glossary). Knowledge, ethical and gender competencies, satisfaction, perceptions, usability and BL acceptance were as-sessed. The BLG showed higher scores than the FLG in knowledge (p=0.011), three ethical/gender competencies (p<0.05), increased motivation to prepare themselves before class (p=0.005), in-creased motivation and ability of thinking (p=0.005), improved understanding of important topics (p=0.015), course organization (p=0.017), educational material (p=0.001), easiness to understand (p=0.007), comprehensive coverage of the subject (p=0.001), and clarity of instructions (p=0.004), whilst usability was acceptable. BL improved knowledge, competencies, perceptions and satis-faction of students. Thus, this study supports the use of BL as a pedagogical approach to foster innovative learning.